Epinephrine in Neonatal Resuscitation - Payam Vali; Deepika Sankaran; Munmun Rawat; Sara Berkelhamer; Satyan Lakshminrusimha (MDPI AG, 2019)
Epinephrine is the only medication recommended by the International Liaison Committee on Resuscitation for use in newborn resuscitation. Strong evidence from large clinical trials is lacking owing to the infrequent use of epinephrine during neonatal resuscitation. Current recommendations are weak as they are extrapolated from animal models or pediatric and adult studies that do not adequately depict the transitioning circulation and fluid-filled lungs of the newborn in the delivery room. Many gaps in knowledge including the optimal dosing, best route and timing of epinephrine administration warrant further studies. Experiments on a well-established ovine model of perinatal asphyxial cardiac arrest closely mimicking the newborn infant provide important information that can guide future clinical trials.